The bleaching of teeth: A review of the literature - Joiner, Andrew (Journal of dentistry, 2006)
To review current knowledge of tooth whitening with respect to external bleaching methods. The scope is the external bleaching of vital teeth and focuses on mechanisms; in vivo and in vitro measurement methods, and factors influencing the efficacy of the whitening process. “Medline” and “ISI Web of Science” databases from 1966 and 1974, respectively were searched electronically with key words tooth, teeth, colo*r, white*, bleach* and peroxide. The importance of tooth whitening for patients and consumers has seen a dramatic increase in the number of products and procedures over recent years, with a concomitant rise in publications on this topic. Literature suggests that the mechanisms of tooth whitening by peroxide occur by the diffusion of peroxide through enamel to cause oxidation and hence lightening of coloured species, particularly within the dentinal regions. A number of approaches are available for measuring changes in tooth colour. These include visual measurements by trained clinicians and instrumental measurements using spectrophotometry, chromameters and digital image analysis. The key factors that affect tooth whitening efficacy by peroxide containing products are concentration and time. In general, higher concentrations are faster than lower concentrations. However, lower concentrations can approach the efficacy of higher concentrations with extended treatment times. Alternative bleach systems to peroxide have received only minor attention. The efficacy of light activated systems versus non-light activated controls in clinical studies is limited and conflicting. Other factors which can influence tooth bleaching outcome include type of stain, initial tooth colour and subject age.